Photoelectric conversion element

A dual-layer hole transport layer with specific materials mitigates deterioration in perovskite-based photoelectric conversion elements, enhancing efficiency retention under heat stress by combining charge injection and recombination resistance materials, achieving a 95% maintenance rate at 85°C.

JP7619425B2Active Publication Date: 2025-01-22MITSUBISHI CHEM CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023208874
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-12-11
Publication Date
2025-01-22
Estimated Expiration
2039-07-30

AI Technical Summary

Technical Problem

The deterioration of the hole transport layer in photoelectric conversion elements using perovskite materials leads to a decrease in photoelectric conversion efficiency, particularly due to charge recombination and charge injection resistance issues, which are not adequately addressed by existing hole transport materials like Spiro-OMeTAD and PTAA.

Method used

A two-layer structure is introduced in the hole transport layer, comprising a charge injection resistance increasing type hole transport material and a charge recombination increasing type hole transport material, with a mass ratio of 1:9 to 9:1, and an ionization energy greater than 4.5 electron volts, to mitigate deterioration and maintain efficiency.

Benefits of technology

The proposed structure effectively suppresses deterioration and maintains high photoelectric conversion efficiency, with a significant improvement in the retention rate of photoelectric conversion efficiency under heat stress, demonstrating a high maintenance rate of 95% or more after exposure to 85°C for extended periods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619425000004
    Figure 0007619425000004
  • Figure 0007619425000005
    Figure 0007619425000005
  • Figure 0007619425000006
    Figure 0007619425000006
Patent Text Reader

Abstract

To provide a photoelectric conversion element capable of suppressing degradation of a hole transport layer generated after a durability test and of suppressing reduction in photoelectric conversion efficiency.SOLUTION: A photoelectric conversion element includes a pair of electrodes, and an electron transport layer, a photoelectric conversion layer, and a hole transport layer that are held by the electrodes. The hole transport layer includes a charge injection resistance increasing type hole transport material and an electric charge recoupling increasing type hole transport material.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a photoelectric conversion element useful as a solar cell. [Background technology]

[0002] Various proposals have been made for photoelectric conversion layers used in solar cell elements (also called photoelectric conversion elements), including silicon semiconductors. Among these, it is known that deterioration of the hole transport layer is a problem in photoelectric conversion elements that use perovskite-type materials (also called PVSK-type materials) as the photoelectric conversion substance. Specifically, this is deterioration of the hole transport layer that occurs after a test in which the element is left in a dark place at 85°C for 240 hours. Deterioration of the hole transport layer naturally leads to a decrease in photoelectric conversion efficiency, so suppressing the decrease in photoelectric conversion efficiency is known to be a challenge.

[0003] As the hole transport material (also called hole transport material) contained in the hole transport layer, 2,2',7,7'-tetrakis(N,N-di-p-methoxyphenylamino)-9,9'-spirobifluorene (Spiro-OMeTAD) is known as the most representative (see, for example, Non-Patent Document 1). However, as described in Non-Patent Document 1, it is known that a photoelectric conversion element containing Spiro-OMeTAD as a hole transport material in the hole transport layer has significant problems with its light resistance and heat resistance for various reasons.

[0004] Polytriarylamine (PTAA) is also known as another representative hole transport material (see, for example, Patent Document 1 and Non-Patent Document 2). Patent Document 1 discloses that solar cells using PTAA as a hole transport material have relatively good durability. Non-Patent Document 2 discloses that a hole transport layer having PTAA is used with a thickness of only 30-50 nm. The reason for this is that although this hole transport material contains an additive such as lithium bis(trifluoromethanesulfonyl)imide in addition to PTAA, the resistivity of this hole transport layer is very high. Therefore, when the film thickness is greater than 50 nm, the resistance of the hole transport layer significantly affects the characteristics of the solar cell element, and the photoelectric conversion efficiency decreases. In the coating process that is usually used in the case of industrially continuously producing large-area modules such as solar cell panels, it is not easy to easily obtain such a thin film with high accuracy.

[0005] Therefore, when the thickness of the hole transport material exceeds 100 nm, an oxidizing agent called a dopant is generally added, and the dopant extracts electrons from the organic semiconductor, which is the main material, to give a positive charge, thereby increasing the electrical conductivity. In the case of PTAA, for example, as shown in Non-Patent Document 3, it is known to use 4-isopropyl-4'-methyldiphenyliodonium tetrakis(pentafluorophenyl)borate (TPFB) as a dopant. However, there has been no sufficient knowledge about the heat resistance of a solar cell element having a hole transport layer using both PTAA and TPFB. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2017-126731 A [Non-patent literature]

[0007] [Non-Patent Document 1] Chemical Review, 2019,1193036-3103 [Non-Patent Document 2] Science Vol.354, Issue6309, pp.206―209 [Non-Patent Document 3] Sci. Adv. 2017;3: e1701293 Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present invention is to suppress the deterioration of a hole transport layer that occurs after a durability test, and to suppress a decrease in the photoelectric conversion efficiency of a photoelectric conversion element. [Means for solving the problem]

[0009] As a result of extensive investigations aimed at solving the above problems, the present inventors have found that there are two types of degradation patterns of hole transport materials. That is, when the above-mentioned Spiro-OMeTAD is subjected to an environmental durability test in a dark place at 60°C and 90RH, degradation occurs as shown in Figure 1. This type of degradation is "charge recombination enhancement type" degradation in which charge recombination occurs at the interface between the photoelectric conversion layer containing the PVSK type material and the hole transport layer. The "charge recombination enhancement type" is a type in which the fill factor is initially 0.65 or more, but as a result of the above-mentioned durability test (60°C 90RH), the fill factor falls to less than 90% of the initial value within 240 hours, and during the same period, the short circuit current and open circuit voltage fall to more than 90% of their initial values, and the series resistance falls to 10 Ωcm 2 Hole transport materials that undergo such degradation are referred to herein as "charge recombination enhanced" hole transport materials.

[0010] Another degradation is shown in FIG. Another type of degradation shown in Figure 2 is when PTAA is used as the hole transport material. Although there is no problem at the interface between the photoelectric conversion layer containing the PVSK-type material and the hole transport layer, the resistance at the interface between the electrode and the hole transport layer increases. This type of degradation is called "charge injection resistance increase type" degradation. The initial series resistance is 10 Ω cm 2 However, the results of the above-mentioned deterioration test (60℃ 90RH) showed that the resistance was 10Ωcm within 240 hours. 2 This degradation is characterized by an increase in the short-circuit current and the open-circuit voltage during the same period, and by the fact that the short-circuit current and the open-circuit voltage maintain 90% or more of their initial values. In this specification, hole transport materials that exhibit this type of degradation are called "charge injection resistance increasing type" hole transport materials.

[0011] Since there are two patterns of deterioration of the hole transport material as described above, it is conceivable to arrange a "charge injection resistance increasing type" hole transport material on the photoelectric conversion layer side of the hole transport layer containing a PVSK type material and an "charge recombination increasing type" hole transport material on the electrode side of the hole transport layer to form a two-layer structure. However, surprisingly, according to the study by the present inventors, by forming the hole transport layer into a mixed layer containing these two types of hole transport material, it was found that the deterioration of both materials was suppressed rather than intermediate performance between the two materials, and this led to the present invention. That is, the gist of the present invention includes the following.

[0012] [1] A semiconductor device comprising a pair of electrodes, an electron transport layer, a photoelectric conversion layer, and a hole transport layer sandwiched between the electrodes, The hole transport layer comprises a charge injection resistance increasing type hole transport material and a charge recombination increasing type hole transport material. [2] The photoelectric conversion element according to [1], wherein the photoelectric conversion layer contains a PVSK-type photoelectric conversion material. [3] The photoelectric conversion element according to [1] or [2], wherein the hole transport layer contains a charge injection resistance increasing type hole transport material and a charge recombination increasing type hole transport material in a mass ratio of 1:9 to 9:1. [4] The photoelectric conversion element according to any one of [1] to [3], wherein the hole transport layer has a mass content of a charge recombination enhancing hole transport material that is greater than the mass content of a charge injection resistance increasing hole transport material. [5] The photoelectric conversion element according to any one of [1] to [4], wherein the ionization energy of at least one of the hole transport materials is greater than 4.5 electron volts. [6] The photoelectric conversion element according to any one of [1] to [5], wherein the hole transport material contained in the hole transport layer includes an organic compound. [7] The photoelectric conversion element according to any one of [1] to [6], wherein the charge injection resistance increasing type hole transport material and the charge recombination increasing type hole transport material are both organic compounds. [8] The photoelectric conversion element according to any one of [1] to [7], wherein the hole transport layer contains an additive. [9] The photoelectric conversion element according to [8], wherein the additive causes a charge transfer reaction with at least one hole transport material before or after the hole transport layer is formed.

[10] The photoelectric conversion element according to any one of [1] to [9], wherein the hole transport layer is formed by a coating method.

[11] The photoelectric conversion element according to any one of [1] to

[10] , wherein the hole transport layer contains a hole transport material having an aromatic amine skeleton.

[12] The photoelectric conversion element according to any one of [1] to

[11] , wherein the hole transport layer contains a hole transport material having a fluorene skeleton.

[13] The photoelectric conversion element according to

[12] , wherein the fluorene skeleton is a part of a spiro skeleton.

[14] The photoelectric conversion element according to any one of [8] to

[13] , wherein the additive contains a boron compound.

[15] The photoelectric conversion element according to

[14] , wherein the boron compound is tetrakis(pentafluorophenyl)borate.

[16] The photoelectric conversion element according to any one of claims 1 to 15, wherein the hole transport layer contains polytriarylamine and Spiro-OMeTAD. Effect of the Invention

[0013] According to the present invention, it is possible to provide a photoelectric conversion element capable of suppressing deterioration of the hole transport layer that occurs after a durability test and suppressing a decrease in photoelectric conversion efficiency. [Brief description of the drawings]

[0014] [Figure 1] 1 is a graph showing the results of a durability test carried out in a dark place at 60° C. and 90 RH on a photoelectric conversion element having a hole transport layer containing Spiro-OMeTAD. [Diagram 2] 1 is a graph showing the results of a durability test carried out in a dark place at 60° C. and 90 RH on a photoelectric conversion element having a hole transport layer containing PTAA. [Diagram 3] FIG. 1 is a diagram illustrating a typical example of a photoelectric conversion element according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention will be described in detail below. However, the description of the constituent elements described below is one example (representative example) of an embodiment of the present invention, and the present invention is not limited to these contents, and can be implemented in various modifications within the scope of the gist of the present invention.

[0016] The photoelectric conversion element according to one embodiment of the present invention includes a pair of electrodes, an electron transport layer, a photoelectric conversion layer, and a hole transport layer sandwiched between the electrodes. The hole transport layer includes a charge injection resistance increasing type hole transport material and a charge recombination increasing type hole transport material. The configuration of the photoelectric conversion element according to this embodiment will be described below with reference to the drawings.

[0017] FIG. 3 is a cross-sectional view showing a schematic diagram of an embodiment of a photoelectric conversion element. The photoelectric conversion element shown in FIG. 3 has a structure of a photoelectric conversion element used in a general thin-film solar cell, but the photoelectric conversion element according to this embodiment is not limited to the structure shown in FIG. 3. In the photoelectric conversion element 100 shown in FIG. 3, a photoelectric conversion layer 103 is located between a pair of electrodes consisting of a lower electrode 101 and an upper electrode 105. In the photoelectric conversion element 100, an electron transport layer 102 is disposed between the lower electrode 101 and the photoelectric conversion layer 103, and a hole transport layer 104 is disposed between the upper electrode 105 and the photoelectric conversion layer 103. Furthermore, as shown in FIG. 3, the photoelectric conversion element 100 may have a base material 106, and may have other layers such as an insulator layer and a work function tuning layer.

[0018] The photoelectric conversion layer 103 is a layer where photoelectric conversion takes place. When the photoelectric conversion element 100 receives light, the light is absorbed by the photoelectric conversion layer 103 to generate carriers. The generated carriers are extracted from the lower electrode 101 and the upper electrode 105.

[0019] In this embodiment, the photoelectric conversion layer 103 may contain an organic-inorganic hybrid semiconductor material. The organic-inorganic hybrid semiconductor material refers to a material in which an organic component and an inorganic component are combined at a molecular level or a nano level, and which exhibits semiconductor properties.

[0020] In this embodiment, the organic-inorganic hybrid semiconductor material may be a compound having a perovskite structure (hereinafter, sometimes referred to as a PVSK-type photoelectric conversion material). The PVSK-type photoelectric conversion material refers to a semiconductor compound having a perovskite structure. There are no particular limitations on the PVSK-type photoelectric conversion material, but for example, the PVSK-type photoelectric conversion material described in Galasso et al. Structure and The PVSK type photoelectric conversion material can be selected from those listed in Properties of Inorganic Solids, Chapter 7 - Perovskite type and related structures. For example, the PVSK type photoelectric conversion material can be an AMX3 type represented by the general formula AMX3 or an A2MX4 type represented by the general formula A2MX4. Here, M represents a divalent cation, A represents a monovalent cation, and X represents a monovalent anion.

[0021] There is no particular restriction on the monovalent cation A, but those described in the above book by Galasso can be used. More specific examples include cations containing elements of Groups 1 and 13 to 16 of the periodic table. Among these, cesium ion, rubidium ion, ammonium ion which may have a substituent, or phosphonium ion which may have a substituent are preferred. Examples of ammonium ions which may have a substituent include primary ammonium ions and secondary ammonium ions. There is no particular restriction on the substituent. Specific examples of ammonium ions which may have a substituent include alkylammonium ions and arylammonium ions. In particular, in order to avoid steric hindrance, monoalkylammonium ions which form a three-dimensional crystal structure are preferred, and from the viewpoint of improving stability, it is preferred to use alkylammonium ions substituted with one or more fluorine groups. In addition, a combination of two or more types of cations can be used as the cation A.

[0022] Specific examples of the monovalent cation A include a methylammonium ion, a methylammonium monofluoride ion, a methylammonium difluoride ion, a methylammonium trifluoride ion, an ethylammonium ion, an isopropylammonium ion, an n-propylammonium ion, an isobutylammonium ion, an n-butylammonium ion, a t-butylammonium ion, a dimethylammonium ion, a diethylammonium ion, a phenylammonium ion, a benzylammonium ion, a phenethylammonium ion, a guanidinium ion, a formamidinium ion, an acetamidinium ion, and an imidazolium ion.

[0023] There is no particular limitation on the divalent cation M, but it is preferably a divalent metal cation or semimetal cation. Specific examples include cations of elements in Group 14 of the periodic table, and more specific examples include lead cations (Pb 2+ ), tin cation (Sn 2+ ), germanium cation (Ge 2+ ) can be mentioned. In addition, a combination of two or more kinds of cations can be used as the cation M. From the viewpoint of obtaining a stable photoelectric conversion element, it is particularly preferable to use a lead cation or two or more kinds of cations including a lead cation.

[0024] Examples of monovalent anions X are halides, acetate, nitrate, and sulfate. Examples of the anion X include borate ions, acetylacetonate ions, carbonate ions, citrate ions, sulfur ions, tellurium ions, thiocyanate ions, titanate ions, zirconate ions, 2,4-pentanedionate ions, and silicofluoride ions. In order to adjust the band gap, X may be one type of anion or a combination of two or more types of anions. In one embodiment, X may be a halide ion, or a combination of a halide ion and another anion. Examples of the halide ion X include chloride ions, bromide ions, and iodide ions. It is preferable to use iodide ions from the viewpoint of not widening the band gap of the semiconductor too much.

[0025] The photoelectric conversion layer 103 contains at least a halide-based PVSK-type photoelectric conversion material in which X is a halide ion or a combination of a halide ion and another anion, and may contain other perovskite semiconductor compounds. For example, the photoelectric conversion layer 103 may contain a PVSK-type photoelectric conversion material in which at least one of A, B, and X is different. The photoelectric conversion layer 103 may also have a laminated structure formed of a plurality of layers containing different materials or having different components.

[0026] Specific examples of halide-based PVSK-type photoelectric conversion materials include CH3NH3PbI3, CH3NH3PbBr3, CH3NH3PbCl3, CH3NH3SnI3, CH3NH3SnBr3, CH3NH3SnCl3, and CH3NH3PbI (3-x) Cl x , CH3NH3PbI (3-x) Br x , CH3NH3PbBr (3-x) Cl x , CH3NH3Pb (1-y) Sn y I3, CH3NH3Pb (1-y) Sn y Br3, CH3NH3Pb (1-y) Sn y Cl3, CH3NH3Pb (1-y) Sn y I (3-x) Clx , CH3NH3Pb (1-y) Sn y I (3-x) Br x , and CH3NH3Pb (1-y) Sn y Br (3-x) Cl x and the above compounds in which CFH2NH3, CF2HNH3, or CF3NH3 is used instead of CH3NH3. Here, x is an arbitrary value of 0 or more and 3 or less, and y is an arbitrary value of 0 or more and 1 or less.

[0027] The amount of the PVSK type photoelectric conversion material contained in the photoelectric conversion layer 103 is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more so that good semiconductor characteristics can be obtained. There is no particular upper limit. The photoelectric conversion layer 103 may contain an additive in addition to the PVSK type photoelectric conversion material. Examples of the additive include inorganic compounds such as halides, oxides, or inorganic salts such as sulfides, sulfates, nitrates, or ammonium salts, or organic compounds.

[0028] There is no particular limit to the thickness of the photoelectric conversion layer 103. In terms of being able to absorb more light, the thickness of the photoelectric conversion layer 103 is 10 nm or more in one embodiment, 50 nm or more in another embodiment, 100 nm or more in yet another embodiment, and 120 nm or more in yet another embodiment. On the other hand, in terms of lowering the series resistance or increasing the charge extraction efficiency, the thickness of the photoelectric conversion layer 103 is 1500 nm or less in one embodiment, 1000 nm or less in another embodiment, and 600 nm or less in yet another embodiment.

[0029] The method for forming the photoelectric conversion layer 103 is not particularly limited, and any method can be used. Specific examples include a coating method and a vapor deposition method (or a co-deposition method). A coating method can be used because the photoelectric conversion layer 103 can be easily formed. For example, a method can be used in which a coating liquid containing a PVSK-type photoelectric conversion material or a precursor thereof is applied, and the photoelectric conversion layer 103 is formed by heating and drying as necessary. In addition, after applying such a coating liquid, a solvent in which the PVSK-type photoelectric conversion material has low solubility can be further applied to precipitate the PVSK-type photoelectric conversion material.

[0030] The precursor of the PVSK-type photoelectric conversion material is the PVSK-type photoelectric conversion material after applying the coating liquid. It refers to a material that can be converted into a PVSK-type photoelectric conversion material by heating. As a specific example, a PVSK-type photoelectric conversion material precursor that can be converted into a PVSK-type photoelectric conversion material by heating can be used. For example, a coating liquid can be prepared by mixing a compound represented by the general formula AX, a compound represented by the general formula MX2, and a solvent, and heating and stirring the mixture. By applying this coating liquid and drying it by heating, a photoelectric conversion layer 103 containing a PVSK-type photoelectric conversion material represented by the general formula AMX3 can be prepared. The solvent is not particularly limited as long as it dissolves the PVSK-type photoelectric conversion material and the additives, and examples thereof include organic solvents such as N,N-dimethylformamide.

[0031] Any method can be used as a method for applying the coating liquid, and examples thereof include spin coating, inkjet coating, doctor blade coating, drop casting, reverse roll coating, gravure coating, kiss coating, roll brush coating, spray coating, air knife coating, wire barber coating, pipe doctor coating, impregnation / coating, and curtain coating.

[0032] [1.2 Electrodes] The electrode has a function of collecting holes and electrons generated by light absorption in the photoelectric conversion layer 103. The photoelectric conversion element 100 according to an embodiment has a pair of electrodes, one of which is called an upper electrode and the other is called a lower electrode. When the photoelectric conversion element 100 has a substrate or is provided on a substrate, the electrode closer to the substrate can be called a lower electrode, and the electrode farther from the substrate can be called an upper electrode. In addition, a transparent electrode can be called a lower electrode, and an electrode less transparent than the lower electrode can be called an upper electrode. The photoelectric conversion element 100 shown in FIG. 3 has a lower electrode 101 and an upper electrode 105.

[0033] The pair of electrodes may be an anode suitable for collecting holes and a cathode suitable for collecting electrons. In this case, the photoelectric conversion element 100 may have a forward configuration in which the lower electrode 101 is an anode and the upper electrode 105 is a cathode, or may have an inverted configuration in which the lower electrode 101 is a cathode and the upper electrode 105 is an anode.

[0034] Either one of the pair of electrodes may be light-transmitting, or both may be light-transmitting. Light-transmitting refers to transmitting 40% or more of sunlight. In addition, a sunlight transmittance of 70% or more of the transparent electrode is preferable so that more light passes through the transparent electrode and reaches the active layer 103. The light transmittance can be measured with a spectrophotometer (e.g., U-4100 manufactured by Hitachi High-Technologies Corporation).

[0035] When the lower electrode and / or the upper electrode are transparent electrodes, the lower electrode and / or the upper electrode may be formed of a single layer of a transparent conductive layer or a metal layer, or may be formed by laminating a transparent conductive layer and a metal layer, as long as it has the above-mentioned visible light transmittance. However, if the transparent electrode is formed only of a transparent conductive layer, the resistance is high and the conversion efficiency may be reduced because it tends not to show good conductivity. In addition, when the transparent electrode is formed only of a thin metal layer, the metal layer is easily corroded and the photoelectric conversion element tends to deteriorate over time, so that the electrode to be the transparent electrode is preferably formed by laminating a transparent conductive layer and a metal layer.

[0036] The material used for the transparent conductive layer is not particularly limited, but may be tin-doped indium oxide (ITO), zinc-doped indium oxide (IZO), tungsten-doped indium oxide (IWO), zinc-aluminum oxide (AZO), indium oxide (In2O3), etc. Among these, it is preferable to use amorphous oxides such as tin-doped indium oxide (ITO), zinc-doped indium oxide (IZO), tungsten-doped indium oxide (IWO), and zinc-tin composite oxide (ZTO).

[0037] Furthermore, the transparent conductive layer preferably has a sheet resistance of 100 Ω / □ or less, more preferably 50 Ω / □ or less, and more preferably 0.1 Ω / □ or more.

[0038] The material of the metal layer is not particularly limited, and examples thereof include metals such as gold, platinum, silver, aluminum, nickel, titanium, magnesium, calcium, barium, sodium, chromium, copper, and cobalt, or alloys thereof. Among these, the material forming the metal layer is preferably silver or a silver alloy, which exhibits high electrical conductivity and has a high visible light transmittance in a thin film. Examples of silver alloys include silver-gold alloys, silver-copper alloys, silver-palladium alloys, silver-copper-palladium alloys, and silver-platinum alloys, which are less susceptible to sulfurization or chlorination and improve the stability of the thin film.

[0039] The film thickness of the metal layer is not particularly limited as long as it can maintain a visible light transmittance of 70% or more as a transparent electrode, but in order to obtain good electrical conductivity, it is preferably 1 nm or more, and more preferably 5 nm or more, while in order to prevent a decrease in the amount of light incident on the active layer due to a decrease in light transmittance, it is preferably 15 nm or less, and more preferably 10 nm or less.

[0040] As described above, if one of the pair of electrodes is a transparent electrode, the other electrode does not necessarily have to be a transparent electrode, and may be a non-transparent electrode. When a non-transparent electrode is used, there is no particular limitation, but for example, the non-transparent electrode can be formed by thickening the metal layer as described above. In addition, when both the lower electrode and the upper electrode are transparent electrodes, it is preferable that both the lower electrode and the upper electrode have a laminated structure of a metal layer and a transparent conductive layer.

[0041] The total thickness of the lower electrode and the upper electrode is not particularly limited and may be arbitrarily selected in consideration of the optical and electrical properties. In particular, in order to suppress the sheet resistance, the film thickness of each of the lower electrode and the upper electrode is preferably 10 nm or more, more preferably 20 nm or more, and even more preferably 50 nm or more, while in order to maintain a high transmittance, it is preferably 10 μm or less, more preferably 1 μm or less, and even more preferably 500 nm or less.

[0042] The method for forming the lower electrode and the upper electrode is not particularly limited, and they can be formed by a known method according to the material used. Examples of the film formation step in coating include vacuum methods such as deposition and sputtering, and wet methods in which ink containing nanoparticles or precursors is applied. The lower electrode and the upper electrode may be surface-treated to improve electrical properties, wettability, and the like.

[0043] [1.3 Hole transport layer] The hole transport layer 104 is a layer located between the photoelectric conversion layer 103 and the electrode 105. The hole transport layer 104 can be used, for example, to improve the efficiency of carrier movement from the photoelectric conversion layer 103 to the upper electrode 105.

[0044] In this embodiment, the hole transport layer includes a charge injection resistance increasing type hole transport material and a charge recombination increasing type hole transport material. A hole transport material with increased charge injection resistance is a hole transport material that exhibits the following degradation: The initial series resistance is 10Ωcm 2 However, as a result of a deterioration test at 60℃ 90RH, it was found to be 10Ωcm within 240 hours. 2 Degradation in which the short-circuit current and open-circuit voltage remain at 90% or more of their initial values ​​during the same period.

[0045] Charge recombination enhanced hole transport materials are hole transport materials that exhibit the following degradation: The initial fill factor is 0.65 or more, but as a result of a durability test at 60°C and 90RH, the fill factor falls to less than 90% of its initial value within 240 hours. During the same period, the short circuit current and open circuit voltage are 90% or more of their initial values, and the series resistance is 10 Ωcm. 2 Keep less than deterioration.

[0046] The charge injection resistance increasing type hole transport material is not particularly limited as long as it causes the above-mentioned deterioration, and may be an organic compound, preferably an organic compound having an aromatic amine skeleton, and typically includes polytriarylamine (PTAA). The charge recombination enhancing hole transport material is not particularly limited as long as it causes the above-mentioned deterioration, and may be an organic compound, preferably an organic compound having a fluorene skeleton, and more preferably the fluorene skeleton is a part of a spiro skeleton, and a typical example is 2,2',7,7'-tetrakis(N,N-di-p-methoxyphenylamino)-9,9'-spirobifluorene (Spiro-OMeTAD).

[0047] The content ratio (mass ratio) of the charge injection resistance increasing hole transport material to the charge recombination increasing hole transport material in the hole transport layer is preferably within a range of 9:1 to 1:9, more preferably within a range of 8:2 to 2:8, and the content by mass of the charge recombination increasing hole transport material is preferably greater than that of the charge injection resistance increasing hole transport material. The content of the hole transport material in the hole transport layer, in terms of the total of the charge injection resistance increasing type hole transport material and the charge recombination increasing type hole transport material, is usually 30% by mass or more, preferably 50% by mass or more, and is usually 100% by mass or less. By setting the content of the hole transport material within the above range, the conductivity of the entire hole transport layer can be kept good, and the initial series resistance and FF can be improved. The ionization energy of the hole transport material contained in the hole transport layer is preferably 4.5 electron volts or more.

[0048] The hole transport layer may contain additives in addition to the hole transport material, such as boron compounds such as tetrakis(pentafluorophenyl)borate, molybdenum compounds such as tris[1-(methoxycarbonyl)-2-(trifluoromethyl)-ethane-1,2-dithiolene]molybdenum, and organic compounds having a tetracyanoquinodimethane skeleton such as 2,3,4,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane. The additive preferably undergoes a charge transfer reaction with at least one hole transport material before or after the hole transport layer is formed. The amount of the additive added in the hole transport layer is usually 0% by mass or more, preferably 0.01% by mass or more, and usually 70% by mass or less, preferably 50% by mass or less. The additive is preferably used when the thickness of the hole transport layer is thick, and is not particularly limited, but is preferably added when the thickness of the hole transport layer is 50 nm or more, particularly 100 nm or more. When the thickness of the hole transport layer is 100 nm or more, the conductivity of the film tends to be insufficient if no additive is contained, so the conductivity of the film can be improved by containing the additive.

[0049] The hole transport layer is preferably formed by a coating method similar to the photoelectric conversion layer, the details of which are as described above in the description of the photoelectric conversion layer. The thickness of the hole transport layer is not particularly limited, but is usually 10 nm or more, preferably 20 nm or more, and is usually 1000 nm or less, preferably 50 nm or less.

[0050] [1.4 Electron transport layer] The electron transport layer 102 is a layer located between the photoelectric conversion layer 103 and the electrode 101. The transport layer 102 can be used, for example, to improve the efficiency of carrier movement from the photoelectric conversion layer 103 to the lower electrode 101 .

[0051] In this embodiment, there is no particular limitation on the constituent members and manufacturing method of the electron transport layer 102, and well-known techniques can be used. For example, the members and manufacturing methods described in known documents such as WO 2013 / 171517, WO 2013 / 180230, and JP 2012-191194 A can be used.

[0052] [1.4 Base material] The photoelectric conversion element 100 generally has a substrate 106 that serves as a support. The material of the substrate 106 is not particularly limited as long as it does not significantly impair the effects of the present invention, and may be any material described in known documents such as International Publication No. WO 2013 / 171517, International Publication No. WO 2013 / 180230, or JP 2012-191194 A.

[0053] [1.5 Other layers] The photoelectric conversion element 100 may have other layers. For example, the photoelectric conversion element 100 may have a work function tuning layer for adjusting the work function of the electrode between the lower electrode 101 and the electron transport layer 102, or between the upper electrode 105 and the hole transport layer 104. The photoelectric conversion element 100 may also have a thin insulator layer between the lower electrode 101 and the photoelectric conversion layer 103, or between the upper electrode 105 and the photoelectric conversion layer 103, for preventing moisture and the like from reaching the photoelectric conversion layer 103. In addition, the photoelectric conversion element 100 may be further sealed to improve durability. For example, the photoelectric conversion element 100 can be sealed by further laminating a sealing plate on the upper electrode 105 and fixing the base material 106 and the sealing plate with an adhesive.

[0054] [2. Method for fabricating photoelectric conversion element] According to the above-mentioned method, the photoelectric conversion element 100 can be manufactured by forming each layer constituting the photoelectric conversion element 100. There is no particular limitation on the method for forming each layer constituting the photoelectric conversion element 100, and the layers can be formed by a sheet-to-sheet method or a roll-to-roll method.

[0055] The roll-to-roll method is a method in which a flexible substrate wound in a roll is unwound and processed while being transported intermittently or continuously until it is wound up by a take-up roll. The roll-to-roll method allows long substrates on the order of kilometers to be processed in one go, making it more suitable for mass production than the sheet-to-sheet method. However, when attempting to deposit each layer using the roll-to-roll method, due to its structure, the film may be scratched or partially peeled off due to contact between the deposition surface and the roll.

[0056] In addition, after laminating the upper electrode 105, the photoelectric conversion element 100 can be heated at a temperature range of 50° C. or more in one embodiment, 80° C. or more in another embodiment, 300° C. or less in one embodiment, 280° C. or less in another embodiment, and 250° C. or less in still another embodiment (this step may be referred to as an annealing step). By performing the annealing step at a temperature of 50° C. or more, the effect of improving the adhesion between each layer of the photoelectric conversion element 100, for example, between the electron transport layer 102 and the lower electrode 101, between the electron transport layer 102 and the photoelectric conversion layer 103, etc., can be obtained. By improving the adhesion between each layer, the thermal stability and durability of the photoelectric conversion element can be improved. By setting the temperature of the annealing step to 300° C. or less, the possibility of thermal decomposition of the organic compound contained in the photoelectric conversion element 100 is reduced. In the annealing step, stepwise heating using different temperatures within the above temperature range may be performed.

[0057] The heating time is 1 minute or more in one embodiment, 3 minutes or more in another embodiment, 180 minutes or less in one embodiment, and 60 minutes or less in another embodiment, in order to improve adhesion while suppressing thermal decomposition. The annealing process can be terminated when the open circuit voltage, short circuit current, and fill factor, which are parameters of the solar cell performance, reach a certain value. In addition, the annealing process can be performed under normal pressure and in an inert gas atmosphere in order to prevent thermal oxidation of the constituent materials. As a heating method, the photoelectric conversion element may be placed on a heat source such as a hot plate, or the photoelectric conversion element may be placed in a heating atmosphere such as an oven. In addition, the heating may be performed in a batch manner or a continuous manner.

[0058] [3. Photoelectric conversion characteristics] The photoelectric conversion characteristics of the photoelectric conversion element 100 can be determined for each light source used as follows. Light is irradiated onto the photoelectric conversion element 100, and the current-voltage characteristics are measured. From the obtained current-voltage curve, photoelectric conversion characteristics such as photoelectric conversion efficiency (PCE), short-circuit current density (Jsc), open circuit voltage (Voc), fill factor (FF), series resistance, and shunt resistance can be determined.

[0059] The light source used to determine the photoelectric conversion characteristics can be sunlight or an artificial light source, such as a halogen lamp, a xenon lamp, a metal halide lamp, a fluorescent lamp, a white LED lamp, an incandescent LED lamp, a mercury lamp, a sodium lamp, or a combination of these lamps.

[0060] Generally, xenon lamps or metal halide lamps are used as light sources for artificial sunlight, and light with conditions similar to the AM1.5G spectrum is emitted at an irradiation intensity of 100 mW / cm. 2 In addition, although there are no particular limitations on the low-illuminance light source, a white LED lamp is used and used as a measurement light source to obtain the photoelectric conversion characteristics at an illuminance of 1 to 5000 Lx.

[0061] The photoelectric conversion efficiency of the photoelectric conversion element 100 is not particularly limited, but is 3% or more in one embodiment, 5% or more in another embodiment, and 8% or more in yet another embodiment. On the other hand, there is no particular limit on the upper limit, and the higher the better. In addition, the fill factor of the photoelectric conversion element 100 is not particularly limited, but is 0.6 or more in one embodiment, 0.7 or more in another embodiment, and 0.8 or more in yet another embodiment. On the other hand, there is no particular limit on the upper limit, and the higher the better.

[0062] The photoelectric conversion element according to this embodiment has a maximum output (Pmax) retention rate of 60% or more, 80% or more in one embodiment, 90% or more in another embodiment, and 95% or more in still another embodiment after being placed in a test environment at a temperature of 85° C. for one day. For example, the Pmax retention rate can be calculated based on the initial Pmax immediately after the photoelectric conversion element is produced and the Pmax after the photoelectric conversion element is placed in the test environment. The Pmax retention rate can also be measured after sealing the photoelectric conversion element as described above. Here, the Pmax retention rate can be calculated as follows based on the Pmax before and after being placed in the test environment. Pmax maintenance rate (%) = ((Pmax after being placed in the test environment) / (Pmax before being placed in the test environment)) x 100

[0063] Furthermore, after being placed in a test environment at a temperature of 85°C for a long period of time (e.g., 60 hours or more), the Pmax retention rate is 40% or more, in one embodiment 60% or more, in another embodiment 80% or more, in yet another embodiment 90% or more, and in yet another embodiment 95% or more.

[0064] The photoelectric conversion element 100 can be suitably used as a solar cell, particularly as a solar cell element of a thin-film solar cell. When used as a thin-film solar cell, a known configuration can be applied. EXAMPLES

[0065] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to the following examples.

[0066] [Preparation of coating solution] (Preparation of Coating Solution for Electron Transport Layer) A 7.5% aqueous dispersion of tin oxide was prepared by adding ultrapure water to a 15% aqueous dispersion of tin oxide (IV) (manufactured by Alfa Aesar).

[0067] (Preparation of Coating Solution for Photoelectric Conversion Layer) Lead iodide (II) was weighed into a vial and introduced into a glove box. N,N-dimethylformamide was added as a solvent so that the concentration of lead iodide (II) was 1.3 mol / L, and then the mixture was heated and stirred at 100°C for 1 hour to prepare coating solution 1 for photoelectric conversion layer.

[0068] Next, formamidine hydroiodide (FAI), methylamine hydrobromide (MABr), and methylamine hydrochloride (MACl) were weighed out in a mass ratio of 10:1:1.5 into another vial and introduced into a glove box. Isopropyl alcohol was added as a solvent to prepare a coating solution 2 for photoelectric conversion layer having a total concentration of FAI, MABr, and MACl of 0.49 mol / L.

[0069] (Preparation of Coating Solution 1 for Hole Transport Layer) 15 mg of poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA, manufactured by our company), 5 mg of [2,2',7,7'-tetrakis(N,N-di-p-methoxyphenylamino)-9,9'-spirobifluorene] (Spiro-OMeTAD, manufactured by Aldrich), and 2.25 mg of 4-isopropyl-4'-methyldiphenyliodonium tetrakis(pentafluorophenyl)borate (TPFB, manufactured by TCI) were weighed into a vial and introduced into a glove box. 0.5 mL of orthodichlorobenzene was added thereto as a solvent. Next, the resulting mixture was heated and stirred at 150°C for 1 hour to prepare coating solution 1 for the hole transport layer.

[0070] [Example 1] A glass substrate (manufactured by Geomatec Co., Ltd.) having a patterned indium tin oxide (ITO) transparent conductive film was subjected to ultrasonic cleaning using ultrapure water, drying by nitrogen blowing, and UV-ozone treatment.

[0071] Next, the coating solution for the electron transport layer prepared as above was spin-coated on the substrate at room temperature at a speed of 2000 rpm to form an electron transport layer with a thickness of about 35 nm, and then the substrate was heated on a hot plate at 150° C. for 10 minutes.

[0072] Next, the substrate was introduced into a glove box, and 150 μL of the photoelectric conversion layer coating solution 1 heated to 100° C. was dropped onto the electron transport layer and spin-coated at a speed of 2000 rpm. Next, the substrate was heated and annealed on a hot plate at 100° C. for 10 minutes to form a lead iodide layer. Next, after the substrate returned to room temperature, the photoelectric conversion layer coating solution 2 (120 μL) was spin-coated onto the lead iodide layer at a speed of 2000 rpm and heated at 150° C. for 20 minutes to form an organic-inorganic perovskite active layer (thickness 650 nm).

[0073] Next, after the substrate returned to room temperature, the hole transport layer coating solution (200 μL) was applied to the photoelectric conversion layer in 100 μL. The solution was spin-coated at a speed of 1,000 rpm and then heated on a hot plate at 90° C. for 5 minutes to form a hole transport layer (170 nm).

[0074] Next, a metal oxide layer was formed by sputtering an IZO film of about 30 nm on the metal layer on the hole transport layer. Furthermore, a metal layer was formed by depositing silver of about 100 nm on the metal oxide layer by resistance heating vacuum deposition, and this metal layer was used as the upper electrode. In this manner, a photoelectric conversion element was produced.

[0075] [Example 2] (Preparation of Coating Solution 2 for Hole Transport Layer) 10 mg of PTAA (manufactured by our company), 10 mg of Spiro-OMeTAD (manufactured by Aldrich), and 2.25 mg of TPFB (manufactured by TCI) were weighed into a vial and introduced into a glove box. 0.5 mL of orthodichlorobenzene was added as a solvent. Next, the resulting mixture was heated and stirred at 150°C for 1 hour to prepare coating solution 2 for the hole transport layer.

[0076] (Creation of photoelectric conversion element) A photoelectric conversion element was prepared in the same manner as in Example 1, except that the hole transport layer was formed using the above-mentioned Coating Liquid 2 for Hole Transport Layer.

[0077] [Example 3] (Preparation of Coating Solution 3 for Hole Transport Layer) 5 mg of PTAA (manufactured by our company), 15 mg of Spiro-OMeTAD (manufactured by Aldrich), and 2.25 mg of TPFB (manufactured by TCI) were weighed into a vial and introduced into a glove box. 0.5 mL of orthodichlorobenzene was added as a solvent. Next, the resulting mixture was heated and stirred at 150°C for 1 hour to prepare coating solution 3 for the hole transport layer.

[0078] (Creation of photoelectric conversion element) A photoelectric conversion element was prepared in the same manner as in Example 1, except that the hole transport layer was formed using the above-mentioned Coating Liquid 3 for Hole Transport Layer.

[0079] [Comparative Example 1] (Preparation of Coating Solution 4 for Hole Transport Layer) 64 mg of poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA) and 7.2 mg of 4-isopropyl-4'-methyldiphenyliodonium tetrakis(pentafluorophenyl)borate (TPFB, manufactured by TCI) were weighed into a vial and introduced into a glove box. 1.6 mL of orthodichlorobenzene was added as a solvent. Next, the resulting mixture was heated and stirred at 150°C for 1 hour to prepare hole transport layer coating solution 4.

[0080] (Creation of photoelectric conversion element) A photoelectric conversion element was prepared in the same manner as in Example 1, except that the hole transport layer was formed using Coating Liquid 4 for Hole Transport Layer.

[0081] [Comparative Example 2] (Preparation of Coating Solution 5 for Hole Transport Layer) 20 mg of [2,2',7,7'-tetrakis(N,N-di-p-methoxyphenylamino)-9,9'-spirobifluorene] (Spiro-OMeTAD, manufactured by Aldrich) and 2 mg of TPFB were weighed into a vial and introduced into a glove box. 0.5 mL of orthodichlorobenzene was added as a solvent to the mixture, and the mixture was heated and stirred at 150° C. for 1 hour to prepare a coating solution 5 for a hole transport layer.

[0082] (Creation of photoelectric conversion element) A photoelectric conversion element was prepared in the same manner as in Example 1, except that the hole transport layer was formed using Coating Liquid 5 for Hole Transport Layer.

[0083] [Evaluation of photoelectric conversion elements] A 1 mm square metal mask was attached to the photoelectric conversion elements obtained in Examples 1 to 3 and Comparative Examples 1 and 2, and the current-voltage characteristics between the ITO electrode and the upper electrode were measured. A source meter (Keithley, Model 2400) was used for the measurements, and the irradiation light source was an air mass (AM) of 1.5 G and an irradiance of 100 mW / cm. 2 From the measurement results, the open circuit voltage Voc (V) and short circuit current density Jsc (mA / cm 2 ), form factor FF, and photoelectric conversion efficiency PCE (%) were calculated. These values, which were calculated based on the measurement results immediately after the photoelectric conversion element was produced, are shown in Table 1.

[0084] [Table 1]

[0085] Here, the open circuit voltage Voc is the current value = 0 (mA / cm 2 ), and the short-circuit current density Jsc is the current density when the voltage value = 0 (V). The form factor FF is a factor that represents the internal resistance, and is expressed by the following equation when the maximum output is Pmax. FF = Pmax / (Voc × Jsc) Furthermore, the photoelectric conversion efficiency PCE is given by the following equation, where Pin is the incident energy. PCE = (Pmax / Pin) x 100 = (Voc × Jsc × FF / Pin) × 100

[0086] The photoelectric conversion elements of Comparative Examples 1 and 2 were sealed by bonding the glass with the central portion dug down and the glass substrate of the photoelectric conversion element with a sealant (photocurable resin), and were left to stand in a dark place at 60° C. for 240 hours. The current-voltage characteristics were measured in the same manner to calculate the photoelectric conversion efficiency PCE, and the photoelectric conversion efficiency retention rate was calculated from the photoelectric conversion efficiency before and after the test. Table 2 shows the photoelectric conversion efficiency retention rate.

[0087] [Table 2]

[0088] In addition, the elements of Examples 1 to 3 and Comparative Example 1 were left to stand in a dark place at a temperature of 85° C. for 240 hours, and the current-voltage characteristics were measured in the same manner to calculate the photoelectric conversion efficiency PCE. The photoelectric conversion efficiency maintenance rate was calculated from the photoelectric conversion efficiencies before and after the test. The photoelectric conversion efficiency maintenance rate is shown in Table 3.

[0089] [Table 3]

[0090] As shown in Table 1, there was no significant difference in the initial conversion efficiency between Examples 1 to 3 and Comparative Examples 1 and 2. Also, as shown in Table 2, it can be seen that the retention rate of the photoelectric conversion efficiency in the heat resistance test at 60 degrees is almost the same between Comparative Example 1 and Comparative Example 2. However, as shown in Table 3, it can be seen that the retention rate of the photoelectric conversion efficiency of Examples 1 to 3 having a hole transport layer in which PTAA and Spiro-OMeTAD are mixed is greatly improved compared to Comparative Example 1 in the heat resistance test at 85 degrees. Among these examples, Example 3 in which the weight mixing ratio of PTAA and Spiro-OMeTAD is 1:3 has the highest retention rate of 0.93, followed by Example 2 in which the weight mixing ratio is 1:1, which has a retention rate of 0.87, and Example 1 in which the weight mixing ratio is 3:1, which has a retention rate of 0.80.

[0091] The reason for this is thought to be that the thermal degradation mechanisms of PTAA and Spiro-OMeTAD are different, and by mixing the two materials, the degradation sites of each material can be complemented. For example, it is thought that PTAA deteriorates more in the area close to the top electrode, while Spiro-OMeTAD deteriorates more in the area closer to the active layer.

[0092] The above results show that by using at least two different semiconductor materials in the hole transport layer, i.e., a hole transport material with increased charge injection resistance and a hole transport material with increased charge recombination, the photoelectric conversion element has a high maintenance rate of photoelectric conversion efficiency (heat resistance). [Explanation of symbols]

[0093] 100 Photoelectric conversion element 101 Lower electrode 102 Electron transport layer 103 Active layer 104 Hole transport layer 105 Upper electrode 106 Base material

Claims

1. The device includes a pair of electrodes, an electron transport layer, a photoelectric conversion layer, and a hole transport layer sandwiched between the electrodes, the hole transport layer includes a layer in which an organic compound having an aromatic amine skeleton and an organic compound having a fluorene skeleton are mixed, The organic compound having an aromatic amine skeleton includes a polytriarylamine.

2. The photoelectric conversion element according to claim 1 , wherein the photoelectric conversion layer contains a PVSK type photoelectric conversion material.

3. 3. The photoelectric conversion element according to claim 1, wherein the hole transport layer contains an organic compound having an aromatic amine skeleton and an organic compound having a fluorene skeleton in a mass ratio of 1:9 to 9:

1.

4. 4. The photoelectric conversion element according to claim 1, wherein at least one of the organic compound having an aromatic amine skeleton and the organic compound having a fluorene skeleton has an ionization energy of 4.5 electron volts or more.

5. 5. The photoelectric conversion element according to claim 1, wherein the organic compound having a fluorene skeleton includes an organic compound having a fluorene skeleton as a part of a spiro skeleton.

6. The photoelectric conversion element according to any one of claims 1 to 5, wherein a mass ratio of the organic compound having an aromatic amine skeleton to the organic compound having a fluorene skeleton in the hole transport layer is within a range of 5:5 to 1:

9.

7. 7. The photoelectric conversion element according to claim 1, wherein the hole transport layer contains an additive.

8. The photoelectric conversion element according to claim 7 , wherein the additive causes a charge transfer reaction between at least one of the organic compound having an aromatic amine skeleton and the organic compound having a fluorene skeleton before or after formation of a hole transport layer.

9. 9. The photoelectric conversion element according to claim 1, wherein the hole transport layer is formed by a coating method.

10. The photoelectric conversion element according to claim 7 , wherein the additive comprises a boron compound.

11. The photoelectric conversion element according to claim 10 , wherein the boron compound is tetrakis(pentafluorophenyl)borate.

12. The photoelectric conversion element according to any one of claims 1 to 11, wherein the hole transport layer contains polytriarylamine and Spiro-OMeTAD.

Citation Information

Patent Citations

  • Perovskite thin-film solar cell with three-dimensional ordered mesopore support layer

    CN104409636A

  • Inverted solar cell and manufacturing method thereof

    JP2016532314A

  • Perovskite solar battery

    JP2017126731A

  • Photoelectric conversion element

    JP2017139376A

  • Methods for making perovskite solar cells having improved hole-transport layers

    US20180005762A1